Screening Cellulolytic Bacteria from the Digestive Tract Snail (Achatina fulica) and Test the Ability of Cellulase Activity - Wijanarka Wijanarka; Endang Kusdiyantini; Sarjana Parman (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
On the research of enzyme production levels observed cellulase produced by bacteria in the digestive tract of the isolation of the Snail (Achatina fulica). Isolation of bacteria based on the ability of bacteria to grow on CMC media. The purpose of this study was to determine cellulase activity by cellulolytic bacteria. Some bacterial isolates were identified as cellulolytic bacteria, they were KE-B1, KE-B2, KE-B3, KE-B4, KE-B5, and KE-B6. Isolates KE-B6 was the best isolates. Furthermore KE-B6 isolates were grown on media production to determine the pattern of growth and enzyme activity. Measurement of cell growth was conducted by inoculating starter aged 22 hours at CMC production of liquid medium. Cellulase enzyme activity measurements was performed by the DNS method. The results showed that the highest activity by new isolate bacteria KE-B6 and its value of the activity of 0.4539 U/mL, growth rate (µ) 0.377/hour and generation time (g) 1.84 hour. This research expected cellulase of producing bacteria were easy, inexpensive and efficient. This enzyme can be used as an enzyme biolytic once expected to replace expensive commercial enzyme. The biotylic enzyme can be applied to strains improvement (protoplast fusion).How to CiteWijanarka, W., Kusdiyantini, E. Parman, S. (2016). Screening Cellulolytic Bacteria from the Digestive Tract Snail (Achatina fulica) and Test the Ability of Cellulase Activity. Biosaintifika: Journal of Biology Biology Education, 8(3), 386-392.